Implementasi Aktivitas Fisik (Jalan Kaki) pada Ketidakstabilan Glukosa Darah pada Pasien Diabetes Melitus Tipe II di Rumah Sakit TK II Putri Hijau Medan - Dilla Novita; Ika Ariyanti; Nina Fentiana (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Diabetes mellitus is a chronic non-communicable disease with a globally increasing incidence. This condition occurs due to insufficient insulin production or ineffective insulin action, resulting in difficulty controlling blood glucose levels. The purpose of this study was to determine whether physical activity (walking) can stabilize blood glucose levels in patients with type II diabetes mellitus at TK II Putri Hijau Hospital, Medan. This research used a descriptive method with a case study design. Data were collected using observation sheets and random blood glucose tests. The subjects were rwo patients with nursing problems related to unstable blood glucose levels in type II diabetes mellitus. The results showed that physical activity (walking) interventions were able to stabilize blood glucose levels in type II diabetes mellitus patients. It can be concluded that performing regular physical activity (walking) helps stabilize blood glucose levels. The study suggests that type II diabetes mellitus patients adopt walking as a non-pharmacological therapy.